PENERAPAN STRATEGI PEMBELAJARAN THE POWER OF TWO (KEKUATAN DUA ORANG) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS VII-B SMP NEGERI 3 TAPUNG - Fadhli Naida (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the result of observation of the researcher on the students of class VII-B SMPN 3 Tapung found some problem that is the lack of interest in student learning, most of the students did not pay attention to the teacher explanation when delivering the learning material, passive students in the learning and ask questions, The student is still low that is only 62.2% reaching KKM that is set that is 75. This research aim to know that the implementation of learning strategy of the power of two can improve result learn Indonesian in student of class VII-B SMP Negeri 3 Tapung learning year 2016/2017. This research was conducted in class VII-B of SMP Negeri 3 Tapung in the odd semester of learning year 2016/2017. This research started from August 2016 until September 2016. The subjects of this class action research were conducted on students of grade VII-B SMP Negeri 3 Tapung. The number of students is 37 people, consisting of 17 sons and 20 daughters. The form of this research is Classroom Action Research (PTK). The classroom action research aims to improve the learning outcomes of Bahasa Indonesia in grade VII-B students at SMPN 3 Tapung with the application of the power of two (two power) learning strategy. The results obtained that the application of learning strategy of the power of two can improve the learning outcomes of Indonesian students in grade VII-B SMP Negeri 3 Tapung 2016/2017 academic year.Student learning outcomes before PTK is 73.5 with less category. Student learning outcomes cycle I average class is 82.0 with enough category. In cycle II the average class is 85.0 with good category.